Delay Discounting and Health Risk Behaviors: A Review and Suggestions for School Based Intervention in Vietnam - Ha, Ho Thu; Minh, Dang Hoang; Weiss, Bahr Weiss (VNU Journal of Science: Education Research, 2019)
Delay discounting is the cognitive process that allows the individual to compare values between an immediate smaller reward and a larger but delayed reward (for instance, an individual is asked to choose between 10,000 dong now and 20,000 dong in a week). Assuming an important role in the field of self-control and decision making related to health reecently, delay discounting can be used to explain why people engage in various health risk behaviors, including unhealthy diet, inactivity, smoking, drinking. These behaviors account for serious consequences as mortality, mental disorders, cardiac diseases, cancer… This article firstly presents the concept of delay discounting and the discount functions. Secondly, it summarizes the evidences for the relationship between delay discounting and health risk behaviors and describes how the discount functions explain these behaviors’ patterns. Finally, it introduces some strategies to reduce delay discounting in order to improve health behaviors and makes suggestions for school-based intervention programs targeting health risk behaviors in Vietnam.